2020
DOI: 10.3390/microorganisms8040533
|View full text |Cite
|
Sign up to set email alerts
|

Social Bacteriophages

Abstract: Despite their simplicity, viruses can display social-like interactions such as cooperation, communication, and cheating. Focusing on bacteriophages, here we review features including viral product sharing, cooperative evasion of antiviral defenses, prudent host exploitation, superinfection exclusion, and inter-phage peptide-mediated signaling. We argue that, in order to achieve a better understanding of these processes, their mechanisms of action need to be considered in the context of social evolution theory,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…In the absence of this signaling moiety, however, the phages are induced to switch into the lytic mode. This finding is revolutionary in the field of sociovirology as it opens a new horizon for the peptide-based decisions for viruses [57,58].…”
Section: Phage Communication Shapes Lytic-lysogenic Decisionmentioning
confidence: 97%
“…In the absence of this signaling moiety, however, the phages are induced to switch into the lytic mode. This finding is revolutionary in the field of sociovirology as it opens a new horizon for the peptide-based decisions for viruses [57,58].…”
Section: Phage Communication Shapes Lytic-lysogenic Decisionmentioning
confidence: 97%
“…Phage restriction occurs such as due to the action of bacterial restriction endonucleases (Korona et al, 1993) or instead CRISPR-Cas systems (Kumar et al, 2015;Strotskaya et al, 2017). Another sort of phage restriction is seen with secondary adsorption, which is the adsorption by phages to already phage-infected bacteria (Abedon, 2015a) and can result in superinfection immunity or superinfection exclusion (Abedon, 1994;Berngruber et al, 2010;Blasdel and Abedon, 2017;Domingo-Calap et al, 2020). Both are mechanisms that kill adsorbing phages and, if expressed by bacterial lysogens, are associated as well with survival of the phage-adsorbed bacterium.…”
Section: Null Phage Impacts On Targeted Bacteriamentioning
confidence: 99%
“…Others have demonstrated that viruses acquired traits that facilitated their collective transmission and enabled them to function as infection units (141). Some phages have also adapted distinct strategies to eject multiple phage genomes into the same bacterial host (142). A notable characteristic of filamentous coliphage f1, for example, is their ability to encapsulate multiple phage genome copies within a single capsid.…”
Section: Spontaneousmentioning
confidence: 99%